2023
DOI: 10.1038/s12276-023-00937-x
|View full text |Cite
|
Sign up to set email alerts
|

ANGPTL4 stabilizes atherosclerotic plaques and modulates the phenotypic transition of vascular smooth muscle cells through KLF4 downregulation

Abstract: Atherosclerosis, the leading cause of death, is a vascular disease of chronic inflammation. We recently showed that angiopoietin-like 4 (ANGPTL4) promotes cardiac repair by suppressing pathological inflammation. Given the fundamental contribution of inflammation to atherosclerosis, we assessed the role of ANGPTL4 in the development of atherosclerosis and determined whether ANGPTL4 regulates atherosclerotic plaque stability. We injected ANGPTL4 protein twice a week into atherosclerotic Apoe−/− mice and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Moreover, in mice, Ang-2 showed increased expression in lesions with intraplaque hemorrhage compared to regions of the lesions without [202]. From other experiments in mice, when Ang-4 protein was injected twice a week into atherosclerotic ApoE−/−mice, Ang-4 reduced atherosclerotic plaque size and vascular inflammation and inhibited atherogenesis [203]. Another study showed that genetic ablation of Ang-4 in adipose tissue results in enhanced plasma lipoprotein lipase (LPL) activity, the rapid clearance of circulating triacylglycerols, increased lipolysis and fatty acid oxidation, and de-creased synthesis, suggesting that a lack of Ang-4 in adipose tissue enhances the clearance of proatherogenic lipoproteins, attenuates inflammation, and reduces atherosclerosis.…”
Section: Angiopoietins In Atherosclerosismentioning
confidence: 80%
“…Moreover, in mice, Ang-2 showed increased expression in lesions with intraplaque hemorrhage compared to regions of the lesions without [202]. From other experiments in mice, when Ang-4 protein was injected twice a week into atherosclerotic ApoE−/−mice, Ang-4 reduced atherosclerotic plaque size and vascular inflammation and inhibited atherogenesis [203]. Another study showed that genetic ablation of Ang-4 in adipose tissue results in enhanced plasma lipoprotein lipase (LPL) activity, the rapid clearance of circulating triacylglycerols, increased lipolysis and fatty acid oxidation, and de-creased synthesis, suggesting that a lack of Ang-4 in adipose tissue enhances the clearance of proatherogenic lipoproteins, attenuates inflammation, and reduces atherosclerosis.…”
Section: Angiopoietins In Atherosclerosismentioning
confidence: 80%
“…In vitro studies have shown that ANGPTL4 can alleviate apoptosis and oxidative stress of bone marrow mesenchymal stem cells induced by hypoxia and alleviate myocardial damage in rats with myocardial infarction 37 . The intervention of ANGPTL4 in AS mice can reduce the proliferation of vascular smooth muscle cells and the progression of atherosclerotic plaque 38 . It has been observed in mice with acute myocardial infarction that the elevated ANGPTL4 level is caused by hypoxia, which has a protective effect on the heart and can even be used to predict the prognosis of the disease 39 .…”
Section: Discussionmentioning
confidence: 99%
“…37 The intervention of ANGPTL4 in AS mice can reduce the proliferation of vascular smooth muscle cells and the progression of atherosclerotic plaque. 38 It has been observed in mice with acute myocardial infarction that the elevated ANGPTL4 level is caused by hypoxia, which has a protective effect on the heart and can even be used to predict the prognosis of the disease. 39 Since ANGPTL4 also plays a role in inhibiting inflammation, its role and mechanism in CAD…”
Section: Early Interventions That Address the Common Risk Factors Andmentioning
confidence: 99%
“…Vascular smooth muscle cells (VSMCs) drive cardiovascular disease (CVD) via phenotype switch [ [1] , [2] ]. It is widely recognized that controlling the phenotypic transition of VSMCs is beneficial for treating CVDs [ [3] , [4] ]. In response to stress or vascular injury, contractile VSMCs can switch to a less differentiated state (synthetic phenotype) to acquire the proliferative, migratory, and synthetic capabilities for tissue reparation [ [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%